A vulnerabilidade da agricultura familiar nos municípios do Ceará: O caso do maciço de Baturité - Sabino, Maria Jordana Costa (2013)
This research aims to analyze the main coounties belonging to the Territory Baturité Rural Massif, Ceará State of Brazil, compared to other cities in this State, according to the vulnerability degree of activities involving family farmers. The methodology consisted first in adopt the construction of a Vulnerability Index of Family Farm Agriculture (IMVAF) by using a sert of ten (10) variables. The Index seeks to measure the degree of vulnerability of Family Farms in all over the cities of Ceará, in order to compare with those estimated to the thirteen (13) counties of Baturité Massif. The study was based on two types of analysis: at first, all the couonties of the Ceará State were analyzed in relation to the degree of vulnerability of Family Farming, through their respective IMVAF. Second it was made a survey in the couonties belonging to regiion of the Baturité Massif in order to conduct the empirical analysis and with results coming from the secondary data. The construction of IMVAF, together with the use of cluster analysis, resulted in formation of three grooups classified according to the degree of vulnerability of the family farms in each county. The results showed that only 22 of 184 (11,96%) counties in the Ceará 11,96% had a low level of vulnerability. The Family Farming in most couties of Ceará State are including in the cluster of medium to high vulnerability. Among the indicators that best differentiated the groups was the variables “entering into the marker”; and “the use of animal traction or mechanical”. The Baturité Massif Rural Territory presented an average IMVAF of 0,632. This value showed do ot to be different from Rural Areas of Ceará State. Of the thirteen counties that belong to the Baturité Massif, only one (Pacoti) showed low IMVAF. In relation to empirical research, it should be noted that the situatin in the farmers visited in the couonties is very delicate, setting up, só short of envisioned by the results obtained by calcuylating the IMVAF. Although there was a time difference between the collecting of primary and secondary data, it can be infered that difficulties are persistent and that in some respects the change of results was negative.